What Determines Self-disclosure to Romantic Partners? - Jelić, Margareta (Array, 2010)
Self-disclosure is an act of revealing something about oneself to others that they otherwise wouldn’t have known. It is an important aspect of every relationship, because intimacy can not be achieved without reciprocal self-disclosure. The aim of this study was to determine predictors of five dimensions of self-disclosure (volume, depth, honesty, intention, and valence) for men and women in a dating relationship. The sample consisted of 161 couples aged between 18 and 40 years. The questionnaire consisted of demographic data, the short version of Experience in Close Relations Inventory (Kamenov and Jelic, 2003), The Revised Self-disclosure Scale, Quality of Marriage Index as well as information on previous romantic relationships (number, duration of the longest relationship and satisfaction with past romantic experiences). We also asked participants how they perceive their parents’ relationship (positive and negative interactions between parents, marital satisfaction and quality of parents’ relationship). Regression analyses were conducted separately for each gender. Results have shown that different dimensions of self-disclosure could be explained with different predicting variables. Although there are some differences between men and women, “intention” is best predicted by relationship quality, “honesty” by relationship quality and attachment, “volume” by attachment, “depth” by previous romantic experiences and “valence” by the perceived relationship between one’s parents.